Environmentalism and global international society - Falkner, Robert 1967- (Cambridge University Press, 2021)
Environmentalism and Global International Society reveals how environmental values and ideas have transformed the normative structure of international relations. Falkner argues that environmental stewardship has become a universally accepted fundamental norm, or primary institution, of global international society. He traces the history of environmentalism's rise from a loose set of ideas originating in the nineteenth century to a globally applicable norm in the twentieth century, which has come to redefine international legitimacy and states' global responsibilities. He shows how this deep norm change came about as a result of the interplay between non-state and state actors, and how the new environmental norm has interacted with the existing primary institutions of global international society, most notably sovereignty and territoriality, diplomacy, international law, and the market. This book shifts the attention from the presentist focus in the study of global environmental politics to the longue durée of global norm change in the greening of international relations
Keywords: Environmentalism / International cooperation / History; Environmental protection / International cooperation / History; International relations